The Childfree Choice: Perspectives from Islamic Law and Indonesian Marriage Law (No. 1 of 1974) - Nur Aziz; Reza Fahlevi Nurfaiz (Transpublika Publisher, 2026)
The childfree phenomenon refers to the conscious choice of individuals or couples not to have children, either biologically or through adoption. In Indonesia, this choice raises legal tensions between personal autonomy and the normative framework of the Marriage Law. Law Number 1 of 1974, as amended by Law Number 16 of 2019, positions marriage as oriented toward family continuity and procreation, yet it does not explicitly mandate childbearing. This study analyzes the childfree phenomenon through two lenses: the legal framework of the Marriage Law and socio-cultural and Islamic perspectives that shape public understanding of marriage and family. Using a qualitative approach with a normative legal method, the study finds that the childfree choice exposes a gap between statutory language and social expectation. While the law emphasizes family continuity, it lacks clear recognition of couples’ decisions to remain childfree, creating potential bias in judicial practice and raising constitutional questions regarding equality, privacy, and self-determination—particularly for women who face social pressures. The interpretive space left by the Marriage Law allows some flexibility for childfree couples, but moral, communal, and religious values often overshadow this statutory neutrality. Ultimately, the childfree phenomenon in Indonesia is both a legal and socio-religious issue. It highlights the need for greater recognition of individual rights within the marital framework while addressing the societal and religious norms that influence perceptions of marriage, family, and reproductive choice.